(3GdGbJUGO GdQbei (B:s (3GdGfJQfJ hGYGOI gjcdI GdGSJKeGQ hGdHhQUGJ hGdHfhc GdGdcJQhfjI (B/s - (3GdfLGQ, aQjOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYjI(B, s, 2007)
(3jYQV gPG GdcJGH GdGbJUGOQ GdQbej GdPj jTjQ COGA GdTQcGJ hGdMcheGJ aj GdbQf GdYTQjf Gdi GdGSJKeGQGJ GdYQHjI hJOghQ YGFOgG hJRGjO eNGWQgG aYdi GdUYjO GdYGdej JJLg GdGSJKeGQGJ GdCLfHjI GdeHGTQI aj GdCUhd GdQCSeGdjI Gdi GdhdGjGJ GdeJMOI GdCeQjcjI hGdjGHGf hcfOG, ceG JJLg CjVG GdGSJKeGQGJ GdCLfHjI ZjQ GdeHGTQI gjcd GdEbJUGO GdQbej(B/ (3GdGfJQfjJ h CYGOI gjcdI GdGSJKeGQ h GdHhQUGJ h GdHfhc GdGdcJQhfjI(B/ (3GdGSJKeGQ (B/(3GdHhQUI GdGdcJQhfjI(B/(3GdSjGSI GdfbOjI GdGdcJQhfjI(B/ (3GdSjGSI GdVQjHjI s
Keywords: (3GbJUGO Ohdj GdcJQhfjs; (3GbJUGO Qbeis; (3GbJUGO YQHj GdcJQhfjs